Gas hydrate destabilization and methane release events in the Krishna–Godavari Basin, Bay of Bengal - Joshi, R. K.; Mazumdar, A.; Peketi, A.; Ramamurty, P. B.; Naik, B. G.; Kocherla, M.; Carvalho, Mary Ann; Mahalakshmi, P.; Dewangan, P.; Ramana, M. V. (Marine and Petroleum Geology, 2014)
Methane release events have been linked to global warming, alteration of the carbon cycle and influence on biota. However, unequivocal evidence of paleomethane release events are limited. We report several negative carbon stable isotope excursions in planktic and benthic foraminifera in a core (MD161-8) from the Krishna-Godavari (K–G) Basin, Bay of Bengal. The most negative δ13C spikes are recorded during the marine isotope stages MIS-4 and at the transition of MIS-5 to 4. Occurrence of highly 13C depleted (average δ13C = −48 ± 2.4‰ VPDB) authigenic high magnesian calcite are also reported within this time window from the core MD161-8. In the present work an unequivocal explanation for the observed 13C depletion in the marine planktic and benthic foraminifera is difficult to achieve solely from the optical/electron microscopy or C–O stable isotope ratio analyses due to possible influence of diagenetic alteration. We attribute the observed episodic methane expulsion events, as inferred from the negative δ13C excursions and earlier reports on the occurrence chemosynthetic bivalves and Mo concentration anomaly to the destabilization of the base of gas hydrate stability zone (BGHSZ). Sea level drop and shale tectonics induced focused fluid flow are the two possible causes of hydrate destabilization discussed here. Shale tectonics were possibly responsible for creating fault systems which acted as the conduit for gas flow through the sediment column and subsequent seepage. Shale and salt tectonics in the passive continental margins being a globally observed phenomenon, its role as an important driving force for enhanced methane emission needs detailed investigation to understand the climatic perturbations through geologic time. Additional evidence of methane emission from site MD161-15 further supports the link between shale tectonics and methane emission.
AAy4wyTimes Cited:2Cited References Count:97

Evidence of paleo-cold seep activity from the Bay of Bengal, offshore India - Mazumdar, A.; Dewangan, P.; Joao, H. M.; Peketi, A.; Khosla, V. R.; Kocherla, M.; Badesab, F. K.; Joshi, R. K.; Roxanne, P.; Ramamurty, P. B.; Karisiddaiah, S. M.; Patil, D. J.; et al. (Geochemistry Geophysics Geosystems, 2009)
We report evidence of paleo-cold seep associated activities, preserved in methane-derived carbonates in association with chemosynthetic clams (Calyptogena sp.) from a sediment core in the Krishna-Godavari basin, Bay of Bengal. Visual observations and calculations based on high-resolution wet bulk density profile of a core collected on board R/V Marion Dufresne (May 2007) show zones of sharp increase in carbonate content (10-55 vol%) within 16-20 meters below seafloor (mbsf). The presence of Calyptogena clam shells, chimneys, shell breccias with high Mg calcite cement, and pyrite within this zone suggest seepage of methane and sulfide-bearing fluid to the seafloor in the past. Highly depleted carbon isotopic values (delta C-13 ranges from -41 to -52% VPDB) from these carbonates indicate carbon derived via anaerobic oxidation of methane. Extrapolated mean calendar age (similar to 58.7 ka B. P.) of the clastic sediments at a depth of 16 mbsf is close to the upper limit of the U-Th based depositional age (46.2 +/- 3.7 and 53.0 +/- 1.6 ka) of authigenic carbonates sampled from this level, thereby constraining the younger age limit of the carbonate deposition/methane expulsion events. The observed carbonate deposition might have resulted from the flow of methane-enriched fluids through the fracture network formed because of shale diapirism.
id: 794; 458FC Times Cited:0 Cited References Count:80Y